Management & Caring for Patients of COPD with COVID-19: A Current Perspective - Mamun, SM AA; Islam, Quazi Tarikul; Sarker, Sana Ullah; Mannan, Sonia (Bangladesh Journal of Medicine, 2021)
Currently passing pandemic of SARS COVE-2, that started on December 2019 has been taken nearly 2.8 million lives till April 2021, with a highest mortality among males, older individuals and patients with comorbidities. COPD patients are included in shielding strategies due to their susceptibilityto virusinduced exacerbations, compromised pulmonary function and highprevalence of associated comorbidities. Based on our existing knowledge, Experience of last one year &Metaanalysis of different study report, thisreview has taken the initiative to find the answer of few key question : FirstlyIs the Covid19 infection causing AECOPD like any other viralinfection.Secondly, do systemic corticosteroids offer protection againstCOVID-19 with COPD ? And, finally , what is the evidence regarding use ofMDI or nebulization & NIV as standard treatment .This up-to-date review will make scope for some of the key issues whichhave significant impact on the long-term outlook for COPD patients in thecontext of COVID-19. Bangladesh J Medicine July 2021; 32(2) : 165-169